Deciphering the role of the MALT1–RC3H1 axis in regulating GPX4 protein stability - Jun Wang; Long Liao; Beiping Miao; Bo Yang; Botai Li; Xuhui Ma; Annika Fitz; Shanshan Wu; Jia He; Qianqian Zhang; Shuyi Ji; Guangzhi Jin; et al. (Proceedings of the National Academy of Sciences, 2025)
Ferroptosis, a unique form of iron-dependent cell death triggered by lipid peroxidation accumulation, holds great promise for cancer therapy. Despite the crucial role of GPX4 in regulating ferroptosis, our understanding of GPX4 protein regulation remains limited. Through FACS-based genome-wide CRISPR screening, we identified MALT1 as a regulator of GPX4 protein. Inhibition of MALT1 expression enhances GPX4 ubiquitination-mediated degradation by up-regulating the E3 ubiquitin ligase RC3H1. Using both rescue assays and functional genetic screening, we demonstrate that pharmacologically targeting MALT1 triggers ferroptosis in liver cancer cells. Moreover, we show that targeting MALT1 synergizes with sorafenib or regorafenib to induce ferroptosis across multiple cancer types. These findings elucidate the modulatory effects of the MALT1–RC3H1 axis on GPX4 stability, revealing a molecular mechanism that could be exploited to induce ferroptosis for cancer therapy.